PROPOSED MARKETING STRATEGY TO INCREASE SALES OF HOODIE CENTER ONLINE SHOP - Apriyanti, Hani
The growth of internet users in Indonesia increased by 8.9%. The development of information technology and the internet can make business easier. The development of the internet social media such as Instagram, Facebook, and Twitter have begun to be used for online buying and selling purposes. This will be an opportunity for Hoodie Center, one of the online businesses in the fashion sector, to be able to take advantage of the use of the internet and social media for business purposes. Moreover, hoodie products are trending among millennials, this will pave the way for Hoodie Center to develop its business. However, when the hoodie product was trending, the Hoodie Center actually experienced a decline in sales. In addition, Hoodie Center has also spent quite a lot of advertising costs. In one year, the cost they spend on advertising is Rp. 80,000,000. However, the amount of advertising costs that have been spent also does not affect the sales of Hoodie Center, they still experience a decline in sales even though they are actively advertising their products. This study aims to analyze the external and internal environment and propose a marketing strategy to increase sales of the Hoodie Center. External environmental analysis is carried out using PESTEL, Porter's Five Forces, competitor analysis, and consumer analysis. From the analysis of the company's external environment, several opportunities and threats outside the company's environment were found that could affect the Hoodie Center business. Internal environmental analysis is carried out using STP analysis, marketing mix analysis, and VRIO. Based on the analysis of the company's internal environment, several aspects are categorized as strengths and weaknesses originating from within the company. SEM-PLS is used as a tool to measure the correlation between variables in this study, which is part of consumer analysis and will then become one of the considerations in making SWOT. The SWOT analysis is carried out by combining the results of the company's external and internal environmental analysis and will be used as the basis for developing the TOWS matrix. Alternative strategies are formulated using the TOWS matrix. Through the TOWS matrix, several strategies are generated that will be implemented by the company.